Database systems for advanced applications : DASFAA 2015 International Workshops, SeCoP, BDMS, and Posters, Hanoi, Vietnam, April 20-23, 2015 : revised selected papers /: DASFAA 2015 International Workshops, SeCoP, BDMS, and Posters, Hanoi, Vietnam, April 20-23, 2015 : revised selected papers. ([2015]) - Unknown
No abstract available